Socio-Economic Analysis of Climate Services in Disaster Risk Reduction: A Perspective on Pacific SIDS - Newth, David; Gooley, Geoff; Gunasekera, Don (Frontiers in Environmental Science, 2021)
This paper explores methods and the key factors influencing socio-economic analysis of the role of climate services in disaster risk reduction, with a regional emphasis on Small Island States (SIDS) in the western tropical Pacific. We analyse the role of traditional benefit-cost analysis especially in the context of evaluating the importance of science-based climate change services (i.e. relevant to current and future climate change over multi-decadal timescales) in disaster risk reduction at a national economy level. Our analysis is premised on a range of relevant social and economic metrics at a national economy scale, including surrogate indicators for specific DRR sensitive sectors in context of both mitigation (transitional risk) and adaptation (physical risk) to climate change. Relative importance of different methodologies of socio-economic analysis (i.e. partial/sectoral vs. economy-wide modelling), gaps in relevant data and information, and the role of the public and private sectors in mobilising resources and capability for facilitating such analysis are explored. Our paper also discusses the issues relating to investing in, producing and undertaking on-ground applications associated with disaster risk reduction using climate change services for both public good and private (-for-profit) benefit outcomes, and provides suggestions for further research to improve socio-economic analysis of CIS impacts.